Search code examples
coqcoq-tacticltac

generalizing expressions under binders


I need to generalize expression under the binder. For example, I have in my goal two expressions:

(fun a b => g a b c)

and

(fun a b => f (g a b c))

And I want to generalize g _ _ c part:

One way to do is to rewrite them first into:

(fun a b => (fun x y =>  g x y c) a b)

and the second into:

(fun a b =>
   f (
       (fun x y =>  g x y c) a b
   ))

And then, to generalize (fun x y, g x y c) as somefun with type A -> A -> A. This will turn my expressions into:

(fun a b => somefun a b)

and

(fun a b => f (somefun a b))

The difficulty here is that the expression I am trying to generalize is under the binder. I could not find either a tactic or LTAC expression to manipulate it. How can I do something like this?


Solution

  • There are two keys to this answer: the change tactic, which replaces one term with a convertible one, and generalizing c so that you deal not with g _ _ c but fun z => g _ _ z; this second key allows you to deal with g rather than with g applied to its arguments. Here, I use the pose tactic to control what function applications get β reduced:

    Axiom A : Type.
    Axiom f : A -> A.
    Axiom g : A -> A -> A -> A.
    Goal forall c, (fun a b => g a b c) = (fun a b => f (g a b c)).
    Proof.
      intro c.
      pose (fun z x y => g x y z) as g'.
      change g with (fun x y z => g' z x y).
      (*   (fun a b : A => (fun x y z : A => g' z x y) a b c) =
           (fun a b : A => f ((fun x y z : A => g' z x y) a b c)) *)
      cbv beta.
      (* (fun a b : A => g' c a b) = (fun a b : A => f (g' c a b)) *)
      generalize (g' c); intro somefun; clear g'.
      (* (fun a b : A => somefun a b) = (fun a b : A => f (somefun a b)) *)
    

    Here is an alternate version that uses id (the identity function) to block cbv beta, rather than using pose:

    Axiom A : Type.
    Axiom f : A -> A.
    Axiom g : A -> A -> A -> A.
    Goal forall c, (fun a b => g a b c) = (fun a b => f (g a b c)).
    Proof.
      intro c.
      change g with (fun a' b' c' => (fun z => id (fun x y => g x y z)) c' a' b').
      (*   (fun a b : A =>
            (fun a' b' c' : A => (fun z : A => id (fun x y : A => g x y z)) c' a' b') a b c) =
           (fun a b : A =>
            f
              ((fun a' b' c' : A => (fun z : A => id (fun x y : A => g x y z)) c' a' b') a
                 b c)) *)
      cbv beta.
      (* (fun a b : A => id (fun x y : A => g x y c) a b) =
         (fun a b : A => f (id (fun x y : A => g x y c) a b)) *)
      generalize (id (fun x y : A => g x y c)); intro somefun.
      (* (fun a b : A => somefun a b) = (fun a b : A => f (somefun a b)) *)